ASSOCIATION BETWEEN RELIGIOSITY AND QUALITY OF LIFE IN WOMEN WITH BREAST CANCER UNDERGOING CHEMOTHERAPY - RELIGIOSITY AND QUALITY OF LIFE IN WOMEN WITH CANCER - Castro e Silva, Igor Marcelo; Barreto, Beatriz Castro e Silva de Albergaria; Pires, Andrea Marques da Silva; de Portela, Yara Maria Cavalcante; Lancellotti, Carmen Lúcia Penteado (ARACÊ, 2024)
Objective: To verify the correlation between religiosity and health-related quality of life in women with breast cancer. Method: Analytical longitudinal, prospective study, conducted between January 2019 and March 2020, on a public hospital in Maranhão. A sociodemographic questionnaire and the instruments EORTC-QLQ-C30, EORTC-QLQ-BR23 and DUREL Scale were applied. The data were verified by the Shapiro-Wilk test, Pearson correlation coefficient and Spearman. Results: Eighty women, mean age 52 years, married, with high school education, white, Catholic participated in the research. A positive correlation was observed between religiosity and quality of life in all stages of chemotherapy treatment. Conclusion: The positive association between religiosity and quality of life in women with breast cancer undergoing chemotherapy was the conclusion of our study. Religiosity is an essential factor of quality of life in oncological diseases.